Pengaruh Pendapatan, Jumlah Nasabah dan Pandemi Covid-19 Terhadap Penyaluran KCA PT Pegadaian (Persero) - Titis Sri Rejeki; Nila Hidayah (Universitas Veteran Bangun Nusantara, 2022)
The aim of the study was to determine the effect of income, number of customers and the covid-19 pandemic on KCA lending at PT Pegadaian (Persero) CP Kudus. This type of research is quantitative comparative study. Data collection was carried out using secondary data on financial reports at PT. Pegadaian (Persero) CP Kudus. then to prove the hypothesis, multiple regression analysis was carried out. Based on the results of the analysis, it can be concluded that income in the first and second years of the covid-19 pandemic had no effect on lending. The number of customers in the first year has a positive and significant effect on lending, whereas in the second year the number of customers has no positive and significant effect on lending. While the covid-19 pandemic in the first year had a positive and significant effect on lending, in the second year the covid-19 pandemic had no positive and insignificant effect on credit distribution.